Menggali Potensi Kampung Wisata Di Kota Yogyakarta Sebagai Daya Tarik Wisatawan - Wisnu Hadi (STIE Pariwisata API Yogyakarta, 2019)
Yogyakarta as a city of culture and education city has a wide variety of tourism potentials that can attract domestic and foreign tourists. One of the potentials is tourist villages scattered in the sub-districts in the city of Yogyakarta. The characteristics of each tourist village can attract to be sold to tourists visiting the city of Yogyakarta. On the basis of this it is considered interesting to be a study material for research with a qualitative descriptive method where the understanding of explanations and findings will be described in the form of description of sentences so that the results of interpretation Critically argumentative based on data obtained from research results. The results of this study stated that the potential of tourist villages in the city of Yogyakarta has a variety of arts, culture, heritage, education, culinary and economics, each of which is a mainstay to always be offered to tourists. The tourist village areas that have art, culture and historical buildings are always become a priority for the development of tourism based on local wisdom by its management. Community empowerment in the tourist village is more emphasized on the economic results that are owned by the tourist village such as culinary and handicraft so that distinctiveness is always sought after by tourists. The participation of the community and the government in the development of tourism in the tourism villages in the city of Yogyakarta has been running synergistically.